Post-COVID-19 Long Hauler Clinical Program: Change in Health-Related Quality-of-Life - Marc Brodsky MD (SAGE Publishing, 2021)
Background and Objective An Integrative Medicine Center created a post-COVID-19 myalgiac encephalomyelitis (ME) program in response to a July 2020 Centers for Disease Control and Prevention document that described fatigue and other functional symptoms. The objective is to present process improvement data on change in health-related quality-of-life (HRQOL) in patients who participated in the "long hauler" program. Methods For process improvement purposes, 39 consecutive patients who participated in the post-COVID-19 ME program from August 2020-August 2021 were asked to complete the 12-Item Short Form Survey (SF-12) before treatment and a month later. Results Twelve participants (31%) completed a baseline and follow-up survey. Mean SF-12 physical component summary scores improved 5 (SD 9) and mental component summary scores improved 4 (SD 9) in patients who completed baseline and follow-up surveys. Case studies of two patients who completed the SF-12 at baseline and after 4 weekly treatments illustrate the program's standardized treatment approach. Conclusion Data collected for process improvement reasons describe changes in HRQOL for participants in a post-COVID-19 ME program. Follow-up practice-based clinical trials may discern optimal approaches for patients with this chronic condition.